IMPLEMENTASI KOMUNIKASI HUMANISTIK GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III DI MI AL-AWWAL PALEMBANG - Haryani Agustina; Nurlaila; Siti Fatima; Aquami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of humanistic communication by teachers in improving the learning motivation of third-grade students at MI Al-Awwal Palembang and analyze the supporting and inhibiting factors in its implementation. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of third-grade homeroom teachers, English teachers, and third-grade students of MI Al-Awwal Palembang. Data analysis used the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. Data validity testing was carried out through triangulation of sources and techniques. The results of the study indicate that the implementation of humanistic communication by teachers is realized through friendly, open, empathetic interpersonal interactions, and respect for students. Teachers provide unconditional acceptance to students, do not blame students when they make mistakes, and provide guidance patiently and gently. Teachers also create a safe and comfortable learning atmosphere so that students are more confident and brave to participate in learning. The implementation of humanistic communication has a positive impact on student learning motivation as seen from increased activeness, enthusiasm, courage to ask questions, and student involvement during the learning process. Supporting factors for the implementation of humanistic communication include friendly teacher attitudes, the use of gentle language, and good interpersonal relationships between teachers and students. Meanwhile, inhibiting factors include differences in student character, varying levels of self-confidence, and the presence of passive students in learning.